Implementasi Aplikasi Online Single Submission Dalam Bentuk Legalitas Usaha Sebagai Wujud Pemberdayaan UMKM Di Desa Bareng - Ellisa Adelia; Lucya Natalie; Firnaz Seiff; Muhammad Sabil Ghifarian; Selvia Selvia; Ubay Huse; Mu’tasim Billah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Online Single Submission (OSS) is an application that functions to make business licenses or business legality online for both micro, medium and large scale businesses. As a form of empowering MSMEs in the Bareng Village, the authors carried out socialization activities regarding the importance of having a business legality or in this case a Business Identification Number (NIB) and also conducted a survey of every MSME actor in the Bareng Village. The purpose of this research is to make it easy for business owners to obtain capital assistance in the form of supporting or supporting tools, capital money, and business development funds. Apart from being used as a business identity, NIB ownership is what brings benefits to business owners. This study uses a qualitative method by surveying every MSME actor and also using a quantitative method. The results of this study explain that NIB can stimulate MSME products so that they have an identity to be recognized by the wider community so that they can prosper MSME actors.